Makna Perjalanan Wisata Bagi Backpacker (Studi Fenomenologi Pada Backpacker Yang Melakukan Perjalanan Wisata Ke Sumatera Barat) - Alfath Fortunately; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Backpacker as a unique and independent trip style with minimal cost, the benefits for backpackers are not just for activities, but more than that, they want to know firsthand and the culture of the places they sail, Backpacker becomes a very trip phenomenon unique. This study aims to reveal the motives Backpacker to travel, the meaning of trip for Backpacker and communication experienced by Backpacker in trip.This study uses qualitative methods with the Phenomenology Alfred Schutz’s Theory and George H Mead Symbolic Interaction theory. Informants were chosen based on Snowball technique is 7 (seven) informants. Data collection techniques were conducted with participant caraguna, in-depth interviews and documentation. Data analysis techniques use interactive data analysis techniques consisting of data, presentation data and deduction of conclusions.The results showed that the first, motive Backpacker in trip, among others; past motives of various media, economic factors and family summary, and motives of the future will come with a sense of satisfaction after traveling, occupational factors, acquiring new knowledge, gaining connections, digging memories, religious goals and introducing Indonesia, West Sumatra specifically The outside world. Second, Travel for Backpacker is a search for identity which is a place to find experience, self-actualization, and travel is a life-saving activity and establish a connection for Backapcker. Third, Backpacker's experience of traveling backpacking is a fun experience of receiving acceptance and support from family, expanding friendship, and gaining popularity while unpleasant experiences are considered expensive hobbies, getting unpleasant treatments such as fraud and illegal levies as well as having difficulty obtaining localized language information different.Keyword : Phenomenology, Interaction symbolic, backpacker